2013
DOI: 10.1158/1541-7786.mcr-12-0699
|View full text |Cite
|
Sign up to set email alerts
|

Mitoxantrone Targets Human Ubiquitin-Specific Peptidase 11 (USP11) and Is a Potent Inhibitor of Pancreatic Cancer Cell Survival

Abstract: Pancreatic ductal adenocarcinoma (PDA) is the fourth leading cause of cancer-related death in the United States, with a 95% five-year mortality rate. For over a decade, gemcitabine (GEM) has been the established first-line treatment for this disease despite suboptimal response rates. The development of PARP inhibitors that target the DNA damage repair (DDR) system in PDA cells has generated encouraging results. Ubiquitinspecific peptidase 11 (USP11), an enzyme that interacts with the DDR protein BRCA2, was rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 52 publications
2
65
0
Order By: Relevance
“…We observed a K m of 0.55 μM which is consistent with K m values reported ranging from 0.12–0.77 μM. 1,16 Comparison of FL-USP11 to the construct lacking the catalytic domain UBL2 containing insert, FLΔUBL2, showed that these constructs display similar kinetic parameters as summarized in Figure 4C. Furthermore, the kinetic parameters for FLΔUBL2 and a construct additionally missing the N-terminal DU domains, CatΔUBL2, were comparable (Figure 4C).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We observed a K m of 0.55 μM which is consistent with K m values reported ranging from 0.12–0.77 μM. 1,16 Comparison of FL-USP11 to the construct lacking the catalytic domain UBL2 containing insert, FLΔUBL2, showed that these constructs display similar kinetic parameters as summarized in Figure 4C. Furthermore, the kinetic parameters for FLΔUBL2 and a construct additionally missing the N-terminal DU domains, CatΔUBL2, were comparable (Figure 4C).…”
Section: Resultssupporting
confidence: 91%
“…12,13 Importantly, USP11 has been shown to exhibit altered expression levels in several types of cancers such as lung and breast cancer, 14,15 and the enzymatic activity of USP11 is inhibited by mitoxantrone which affects pancreatic cancer cell survival. 16 There is currently no structure for USP11 domains or information on how its catalytic activity is regulated and substrate is recognized.…”
mentioning
confidence: 99%
“…Recently, mitoxantrone was identified as a USP11 inhibitor. 34 Consistently, USP11 inhibition by mitoxantrone induced cIAP2 destabilization, which was reversed with MG132 treatment (Figures 4h-i). USP11 depletion by siRNA abrogated mitoxantrone-induced cIAP2 degradation, suggesting that mitoxantrone regulates cIAP2 degradation via USP11 inhibition (Figure 4j).…”
Section: Resultssupporting
confidence: 64%
“…USP1, USP1-UAF1, USP46-UAF1 and USP11 were generated as previously described 21,48 . Ub-PCNA was prepared as previously reported 49 .…”
Section: Methodsmentioning
confidence: 99%